Current Population Survey: Voter Supplement File, 1982 ([Verlag nicht ermittelbar], 1984)
This data collection supplies standard monthly labor force data for the week prior to the survey. Comprehensive information is given on the employment status, occupation, and industry of persons 14 years old and older. Additional data are available concerning weeks worked and hours per week worked, reason not working full-time, total income and income components, and residence. Besides the CPS core questions, this survey gathered additional data on citizenship, voter registration, and voter participation in the 1982 congressional elections. Information on demographic characteristics, such as age, sex, race, marital status, veteran status, household relationship, educational background, Hispanic origin, and number and ages of children in household, is available for each person in the household enumerated.